Financing Small and Medium Enterprises in the Republic of South Africa - Fuchs, Michael; Iacovone, Leonardo; Jaeggi, Thomas; Napier, Mark; Pearson, Roland; Pellegrini, Giulia; Villegas Sanchez, Carolina (World Bank, Washington, DC, 2013)
Numerous studies worldwide have highlighted the important contribution made by small and medium-sized enterprises (SMEs) to employment, income and economic growth. In a study of 76 developed and developing economies, Ayyagari and others (2007) found that SMEs account for more than 60 percent of total manufacturing employment and that SMEs contributed significant proportions of Gross Domestic Product (GDP). SME growth requires external financing, but constraints to accessing credit, consistently rated as some of the greatest barriers to the operation and growth of firms, affect SMEs more severely than large firms (Beck and Demirguc-Kunt 2006; Beck and others 2006). The purposes of this report are to: a) analyze the availability of bank finance to SMEs in South Africa and how availability might be enhanced in the context of the economic downturn; and b) offer concrete policy recommendations on how to lessen obstacles to bank SME financing and reduce the negative effects of the economic downturn (or of a similar downturn in future) on access to finance. The report is structured in 5 sections: section two provides a short overview of existing studies and data on SME finance in South Africa. Section three presents the main results of the surveys. Section four provides policy considerations. Section five concludes.